2011
DOI: 10.4314/sljbr.v3i1.66651
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Helminthiasis among School Children in Ilie, Osun State, Southwest, Nigeria

Abstract: A cross sectional study of intestinal helminthiasis among school pupils was undertaken in three primary schools in Ilie in Olorunda Local Government Area of Osun state in order to determine the prevalence and intensity of helminthic infections. The relationship between intestinal helminths and anthropometric indices and the factors that could favour the infection were also studied. Faecal samples from three hundred and four (304) randomly selected out of the four hundred and seven (407) school children in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 14 publications
13
22
1
Order By: Relevance
“…This was probably due to contamination of soil with faecal material. Similar studies reported such agents being responsible for transmission of helminths parasites [15][16][17][18]. The significant association between the presences of human/animal faeces in the vicinity of homes is of great concern and indicates a need for regular environmental sanitation and inspection of in the study area.…”
Section: Discussionsupporting
confidence: 57%
“…This was probably due to contamination of soil with faecal material. Similar studies reported such agents being responsible for transmission of helminths parasites [15][16][17][18]. The significant association between the presences of human/animal faeces in the vicinity of homes is of great concern and indicates a need for regular environmental sanitation and inspection of in the study area.…”
Section: Discussionsupporting
confidence: 57%
“…Other reasons for the disparities in prevalence between both categories of communities could be related to educational attainment status, standard of personal and environmental hygiene and probably social habits [22]. Our findings shows that knowledge, attitude, and practices associated with STH transmission between communities with full and part implementation of WASH intervention was poor.…”
Section: Discussionmentioning
confidence: 60%
“…In Ethiopia, intestinal helminths are resulted from poor environmental sanitation, unsafe human waste disposal systems, lack of safe water supply and low socio-economic status of the country [1318]. The main reason for their persistent presence everywhere is due to frequently low rank in the list of priorities in public health programs because the effect of helminthic infections are not directly measured explicitly in terms of mortality figures [19].…”
Section: Introductionmentioning
confidence: 99%